2022
DOI: 10.3389/fbioe.2021.829821
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced Mechanical Properties of Polyvinyl Chloride-Based Wood–Plastic Composites With Pretreated Corn Stalk

Abstract: Wood–plastic composites (WPCs) are a type of environmentally friendly materials widely used in daily life. This paper selected low-value biomass, corn stalk (CS), as the lignocellulosic resource for polyvinyl chloride (PVC)-based WPCs. To depict the relationship between lignocellulosic composition (cellulose, hemicellulose, and lignin) and mechanical performance of WPCs, pretreatments have been optimized to selective removal of lignin using an alkaline-EtOH stewing process and selective removal of hemicellulos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Based on DTG curves after fibrillation, a maximum degradation temperature shifted to a higher temperature, from 314 °C to 328 °C, indicating an increase in cellulose content owing to partial removal of hemicellulose (Figure 4b). [44,45]…”
Section: The Composition and Thermal Stability Of Eopp-ilmentioning
confidence: 99%
“…Based on DTG curves after fibrillation, a maximum degradation temperature shifted to a higher temperature, from 314 °C to 328 °C, indicating an increase in cellulose content owing to partial removal of hemicellulose (Figure 4b). [44,45]…”
Section: The Composition and Thermal Stability Of Eopp-ilmentioning
confidence: 99%
“…The weak mechanical performance of maize straws is mainly attributed to their higher hemicellulose and lignin content. 3 Hence, for improving the mechanical performance of maize straws, acid treatment, 13,14 alkali treatment, 13,[15][16][17][18][19] silane coupling agent (SCA) treatment, 13,15,16,20 and titanate coupling agent treatment 13 have been used to modify maize straws. In our previous work, 3 chemical modification (NaOH and Na 2 SO 3 mixed aqueous solution) combined with hot pressing was used to fabricate a kind of densified maize straw with ultra-high strength.…”
Section: Introductionmentioning
confidence: 99%
“…A portion of hemicellulose and lignin was removed by chemical modification, and then the structure of maize straws was densified by hot pressing. Moreover, Ying and coworkers further studied the influence of cellulose, hemicellulose, and lignin of maize straws on the mechanical performance of polyvinyl chloride (PVC)/maize straws composites, which indicated that the removal of hemicellulose and lignin of maize straws was benefit to fabricate high‐performance PVC/maize straws composites 18 . Therefore, it is possible to promote the application and utilization of wasted maize straws by chemical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Composites are mixtures of two or more different materials that possess superior properties compared to those of individual materials that participate in the fabrication of composites [ 19 , 20 ]. The investigations of corn stalk waste reinforced composites have pulled in due thought from academicians and industrialists for their unrivalled properties such as improved mechanical characteristics, reduced density, biodegradability and eco-accommodating materials [ [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ] ( Table S1 ). Chen et al [ 29 ] utilised corn stalk flour and hybridized it with sisal fibres for the fabrication of PVC based composites.…”
Section: Introductionmentioning
confidence: 99%